Multinational Study of the Efficacy and Safety of Humanized Anti-HER2 Monoclonal Antibody in Women Who Have HER2-Overexpressing Metastatic Breast Cancer That Has Progressed After Chemotherapy for Metastatic Disease. Issue 8 (10th March 2023) - Cobleigh, Melody A.; Vogel, Charles L.; Tripathy, Debu; Robert, Nicholas J.; Scholl, Susy; Fehrenbacher, Louis; Wolter, Janet M.; Paton, Virginia; Shak, Steven; Lieberman, Gracie; Slamon, Dennis J.
Abstract : PURPOSE: Overexpression of the HER2 protein occurs in 25% to 30% of human breast cancers and leads to a particularly aggressive form of the disease. Efficacy and safety of recombinant humanized anti-HER2 monoclonal antibody as a single agent was evaluated in women with HER2-overexpressing metastatic breast cancer that had progressed after chemotherapy for metastatic disease. PATIENTS AND METHODS: Two hundred twenty-two women, with HER2-overexpressing metastatic breast cancer that had progressed after one or two chemotherapy regimens, were enrolled. Patients received a loading dose of 4 mg/kg intravenously, followed by a 2-mg/kg maintenance dose at weekly intervals. RESULTS: Study patients had advanced metastatic disease and had received extensive prior therapy. A blinded, independent response evaluation committee identified eight complete and 26 partial responses, for an objective response rate of 15% in the intent-to-treat population (95% confidence interval, 11% to 21%). The median duration of response was 9.1 months; the median duration of survival was 13 months. The most common adverse events, which occurred in approximately 40% of patients, were infusion-associated fever and/or chills that usually occurred only during the first infusion, and were of mild to moderate severity. These symptoms were treated successfully with acetaminophen and/or diphenhydramine. The most clinically significant adverse event was cardiac dysfunction, which occurred in 4.7% of patients. Only 1% of patients discontinued the study because of treatment-related adverse events. CONCLUSION: Recombinant humanized anti-HER2 monoclonal antibody, administered as a single agent, produces durable objective responses and is well tolerated by women with HER2-overexpressing metastatic breast cancer that has progressed after chemotherapy for metastatic disease. Side effects that are commonly observed with chemotherapy, such as alopecia, mucositis, and neutropenia, are rarely seen.